Delivering healthcare remotely to cardiovascular patients during COVID-19: A rapid review of the evidence. (August 2020) - Neubeck, Lis; Hansen, Tina; Jaarsma, Tiny; Klompstra, Leonie; Gallagher, Robyn
Background: Although attention is focused on addressing the acute situation created by the COVID-19 illness, it is imperative to continue our efforts to prevent cardiovascular morbidity and mortality, particularly during a period of prolonged social isolation which may limit physical activity, adversely affect mental health and reduce access to usual care. One option may be to deliver healthcare interventions remotely through digital healthcare solutions. Therefore, the aim of this paper is to bring together the evidence for remote healthcare during a quarantine situation period to support people living with cardiovascular disease during COVID-19 isolation. Methods: The PubMed, CINAHL and Google Scholar were searched using telehealth OR digital health OR mHealth OR eHealth OR mobile apps AND COVID-19 OR quarantine search terms. We also searched for literature relating to cardiovascular disease AND quarantine. Results: The literature search identified 45 potentially relevant publications, out of which nine articles were included. Three overarching themes emerged from this review: (1) preparing the workforce and ensuring reimbursement for remote healthcare, (2) supporting mental and physical health and (3) supporting usual care. Conclusion: To support people living with cardiovascular disease during COVID-19 isolation and to mitigate the effects of quarantine and adverse effect on mental and physical well-being, we should offer remote healthcare and provide access to their usual care.